The Effect of Human Capital on Economic Growth in Islamic Economic Perspective: Evidence from Bandung Regency - Ginan Wibawa; Rizzal Muttaqin; Fitriana Dewi Sumaryana (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2021)
The purpose of this study was to analyze the effect of human capital on economic growth in Bandung Regency. This research uses a quantitative approach with multiple linear regression analysis. The data used are secondary data from BPS for the period 2010-2019. Human capital is represented by education by measuring the average length of schooling and health by measuring life expectancy, while economic growth uses per capita GRDP. The results of the analysis with a significance level of 5% indicate that education and health have a positive and significant influence on economic growth in Bandung Regency. It shows the valuable role of human capital as one of the central sources to encourage regional economic development. Economic growth, that main focus is on human development, is following Islamic economic growth principles. So that economic development must be oriented to improving human dignity as a whole.